Exploring parent-athlete sport related communication outside of the sport environment with the Electronically Activated Recorder. (May 2021) - Sutcliffe, Jordan T.; Herbison, Jordan D.; Martin, Luc J.; McLaren, Colin D.; Slatcher, Richard; Benson, Alex J.; Van Woezik, Rachel; Boardley, Ian D.; Carré, Justin M.; Côté, Jean; Bruner, Mark W.
Abstract: Objectives: The purpose of the current study was to explore parent-athlete sport-related conversations as they naturally occurred in the private contexts that surround youth sport. A secondary aim was to understand whether male and female guardians communicate differently in sport, and whether these differences are shaped by the contexts in which they appear. Design: We used the Electronically Activated Recorder (EAR) to gather snippets of parents' and athletes' daily social interactions in the contexts that surround youth sport. A total of 220 audio files were gathered in the car ride to and from competition, the ice hockey arena, and at their home base (i.e., family residence of local teams and hotels for out-of-town teams) over the course of a 3-day competitive ice hockey tournament. Conversations were inductively coded using reflexive thematic analysis through a critical realist lens. Results: Higher order themes included (a) performance-related dialogue; (b) the opportunity to discuss other social agents, and (c) parental social support. Frequency analysis revealed more instances of negative evaluations and technical instruction from fathers, whereas positive encouragement was more prominent from mothers. Conclusion: These findings present novel insight into the nature of parent-athlete interactions outside of the immediate sport-competition environment. We encourage scholars to consider the EAR for future investigation of the youth sport environment. Highlights: Family conversations were gathered in the car, at home, and at the hockey rink. Performance evaluations and technical instruction were more prevalent from fathers. Mothers provided more positive encouragement. Family conversations focus on performance, other social agents, and social support.